Detection of Bacterial Population in Air Conditioner and Determine the Ability to Produce Biofilm - Rahman, Sanaa (Iraqi Journal of Science, 2019)
There is not enough studies about bacterial contamination of air condition system in the cars and houses, bacterial detection of such surrounding is necessary for the human environment. The object of recent study was to evaluate the level of bacterial contamination in air conditioner in cars and houses in Baghdad city, Iraq. Air samples were taken indoor from cars and house air conditioner in the Baghdad city. The result indicated that gram positive bacteria more than gram negative bacteria in air conditioner. Air condition of cars (20-500 CFU) was more contaminated than of houses (10-100 CFU). Bacillus was the most frequently bacterial isolates genus with recovery rate Bacillus spp.32%(10isolates)followed by Staphylococcus epidermis 16%(5 isolates) ,Staphylococcus aureus 16%(5 isolates),Streptococcus pyogens 12.9%(4 isolates) ,Klebsiella pneumeniae 12.9%(4 isolates) and Psudomonas aeruogenosa 9.6%( 3 isolates). The results of biofilm formation test by congored agar found that all bacterial species were biofilm producer.